The Influence of Product Variations, Brand Image and Word of Mouth on Repurchase Interest in Thirsty Drinks at Sentosa Depok Outlets - Priska Restiana Suriadi; Resti Hardini; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2023)
This study aims to determine the influence between product variations, brand image and word of mouth on repurchase interest in HAUS drinks at Sentosa Depok outlets The sample studied in this study amounted to 100 respondents, data collection methods using questionnaire methods with Likert scales and data analysis techniques using Multiple Linear Analysis using SPSS program version 23. The results of the study have a regression equation Y = 0.229 Product Variation + 0.375 Brand Image + 0.326 Word Of Mounth. Based on the results of the T Test, it shows the influence between Product Variation (X1) on Repurchase Interest (Y) based on T count 3. 014 > 1,660 and sig value 0.003 < 0.50.For Brand Image (X2) has a significant influence on Repurchase Interest (Y) based on T count 4,307 < 1,660 and sig value 0.000 < 0.50 Ha. For the variable Word Of Mouth (X3) shows an influence on Repurchase Interest (Y) based on the calculated T value of 3,900 > 1,660 and the sig value of 0.000 < 0.50 The results of this study have concluded that the variables Product Variation, Brand Image and Word of Mouth have a significant effect against Repurchase Interest.